'It's the way you talk to them.' The child's environment: Early Years Practitioners' perceptions of its influence on speech and language development, its assessment and environment targeted interventions. (October 2014) - Marshall, Julie; Lewis, Elizabeth
Speech and language delay occurs in approximately 6% of the child population, and interventions to support this group of children focus on the child and/or the communicative environment. Evidence about the effectiveness of interventions that focus on the environment as well as the (reported) practices of speech and language therapists (SLTs) and other Early Years Practitioners (EYPs) in this regard are limited. One-to-one, semi-structured interviews were carried out with 12 EYPs from one city in North England in order to reveal their beliefs about the impact of the child's environment on language development and how they report assessing and intervening where they have concerns about child language development, in children aged from birth to 5;11 (5 years, 11 months). Interviews were analysed thematically. Results are presented as three themes: (1) environmental influences on language development (people, physical objects, experiences and opportunities, the auditory environment); (2) assessment of the child's environment, including how and what assessment is carried out; and (3) the interventions provided, including what interventions (interaction with children, the physical environment and play) and how they are carried out (strategies, individualization of intervention, sensitivity and modelling). Implications for services are discussed, including increasing parental awareness of the importance of early language input, the perceived value of home-based assessment, sensitivity in referral and individualized interventions. There remains a need to test out practitioners' expressed beliefs and practices and their impact on child language outcomes.